Antagonistic Activity and Production of Antifungal Compound(s) from Selected Trichoderma spp. - ayad Al-Obaidy; Omar Al-Obaidy; Maha Akram Al-Rijabo (College of Education for Pure Sciences, 2010)
ABSTRACT Two Trichoderma spp. (T.harzianum and T.viride) which are well known for their use as biocontrol agents were used in this study and tested for their antagonistic activity against several plant pathogenic (and even human pathogenic) fungi, also the activity was tested against selected Gram positive and Gram negative bacteria. The proper conditions for the production of the antifungal compound were determined, and after the production and extraction of the antifungal compounds from the two Trichoderma spp., an attempt to partially characterize the nature of the antifungal compound(s) was done using several chemical analysis methods, and the results showed that the inhibition was due to the production of antifungal compounds that had many similar characteristics for both T.harzianum and T. viride but with a difference in their antifungal actions.